2017
DOI: 10.1097/tp.0000000000001494
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Pretransplant HLA Antibodies Does Not Impact the Development of Chronic Lung Allograft Dysfunction or CLAD-Related Death

Abstract: Although in previous studies we have shown an increased incidence of antibody-mediated rejection in patients with pretransplant DSA, neither the presence of HLA antibodies nor DSA translated to an increased risk of allograft dysfunction or death if prospective crossmatch testing was negative. Prospective studies are needed to define the impact of pretransplant sensitization on lung transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Bharat et al reported that PGD is associated with an inflammatory cascade that augments the anti-HLA response that predisposes patients to BOS. Based on many previous studies as well as the results of this study, an immunological response may be one of the mechanisms among the multifactorial causes of PGD [26]. Similar results have been reported for other solid organ transplant types.…”
Section: Discussionsupporting
confidence: 89%
“…Bharat et al reported that PGD is associated with an inflammatory cascade that augments the anti-HLA response that predisposes patients to BOS. Based on many previous studies as well as the results of this study, an immunological response may be one of the mechanisms among the multifactorial causes of PGD [26]. Similar results have been reported for other solid organ transplant types.…”
Section: Discussionsupporting
confidence: 89%
“…Bharat et al reported that PGD is associated with an inflammatory cascade that augments the anti-HLA response that predisposes patients to BOS. Based on many previous studies as well as the results of this study, an immunological response may be one of the mechanisms among the multifactorial causes of PGD [ 26 ].…”
Section: Discussionmentioning
confidence: 87%
“…Luminex assay is more sensitive than the conventional CDC method [ 23 25 ]. A recent report by Goldberg et al on the basis of results using Luminex assays showed that 30% of subjects had circulating class I HLA antibodies alone, 4% Class II, and 14.4% class I and class II at MFI > 1000 [ 26 ]. According to Chung et al, of 129 patients who were waiting for a kidney transplant in Korea, 56 patients (43.4%) had PRA ≥ 20% by solid phase Luminex PRA, 45 patients (34.9%) had anti-HLA antibodies based on a Luminex single antigen assay, and 25 patients (44.6%) had HLA-DSA [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies suggest that the pre-transplant detection of circulating DSA is not associated with an increased risk of developing CLAD or related death if prospective cross-match testing was negative (11, 12). The pretransplant detection of DSA and antibodies directed againd non-HLA antigens such as angiotensin type 1 receptor (AT1R) and endothelin type A receptor (ETAR) is reported to have a negative impact on lung transplant outcome (13).…”
Section: Introductionmentioning
confidence: 99%